Effects of Involuntary Smoking and Vaping on the Cardiovascular System - Manfred Neuberger (International Journal of Occupational and Environmental Medicine, 2019)
In deaths and diseases attributed to tobacco smoke cardiovascular events exceed cancer and respiratory diseases. Second hand smoke promotes the development of arteriosclerosis and can trigger acute changes of endothelial function and blood coagulability. Indoor smoking bans reduced coronary syndrome and myocardial infarction 10-20% within one year and were followed by sustainable decreases of stroke and diabetes. With a smoke-free hospitality industry people recognized tobacco smoke as an air pollutant, smoking in public was denormalized and social acceptance of smoking in front of children and pregnant women decreased also in homes and cars. Combined effects with ambient air pollution are proven for active smoking and suspected for SHS. Contamination with third hand smoke (THS) persists for months in homes and cars, creating secondary pollutants that in some cases are more toxic (e.g. nitrosamines). Remnants found in air, dust, and on surfaces (carpets, wallpapers, upholstery, soft toys) were associated with their metabolites in saliva of children and in urine of nonsmokers residing in homes previously occupied by smokers. In animal experiments effects of THS were found on thrombogenesis, insulin resistance through oxidative stress, on the developing immune system, lipid metabolism and alterations in liver, lung, skin and behavior. Much less is known about health effects for bystanders from the aerosols exhaled during “vaping” of e-cigarettes, but nicotine and other toxins from e-cigarettes are certainly a hazard, which should be prevented by the use of dermal and oral nicotine products, which are safer for nicotine replacement and without risk for bystanders.
Keywords: Cardiovascular